Impact Of Information Technology On Fast Food Supply Chain Performance: The Moderating Role Of Information Sharing (Journal of Namibian Studies : History Politics Culture, 2023)
The objective of the study is to demonstrate the influence of information technology on fast food supply chain performance through information sharing. Research data were collected by quota sampling, with a sample size of 210 fast-food businesses in Vietnam. The authors combined qualitative methods and quantitative methods to reach the research objectives. Applying the structural equation modeling (SEM), the research has proven that information technology has a positive effect on information sharing, thereby positively impacting the performance of fast food supply chains. Research results have confirmed the essential role of information technology in fast food supply chain performance.